A New Trend in Oral Sustained Release Technology - Bansal, B. K.; Shakya, V; Rewar, S. (Asian Journal of Pharmaceutical Research and Development, 2014)
In all drug delivery system, Oral drug delivery remains the most preferred system for administration of various drugs. The sustained released dosage forms means that a single dose of a drug that is released over an extended period of time instead of numerous doses is now a day’s area of interest for formulation scientists in Pharmaceutical industry. Ranitidine has been formulated as sustained release matrix tablets. Sustained release is also providing promising way to decrease the side effect of drug by preventing the fluctuation of therapeutic concentration of the drug in the body. Sustained release system are considered a wiser approach for the drugs with short half-lives and which require repeated dosing, they are easy to formulate and are irrespective of absorption process from gastrointestinal tract after oral administration. Hydrophilic polymers have become product of choice as an important ingredient for formulating sustained release formulations. This article contains the basic information regarding design sustained release formulation.